Conjugate calculation of a film-cooled blade for improvement of the leading edge cooling configuration - Norbert Moritz; Karsten Kusterer; Dieter Bohn; Takao Sugimoto; Ryozo Tanaka; Tomoki Taniguchi (Propulsion and Power Research, 2013)
Great efforts are still put into the design process of advanced film-cooling configurations. In particular, the vanes and blades of turbine front stages have to be cooled extensively for a safe operation. The conjugate calculation technique is used for the three-dimensional thermal load prediction of a film-cooled test blade of a modern gas turbine. Thus, it becomes possible to take into account the interaction of internal flows, external flow, and heat transfer without the prescription of heat transfer coefficients. The focus of the investigation is laid on the leading edge part of the blade. The numerical model consists of all internal flow passages and cooling hole rows at the leading edge. Furthermore, the radial gap flow is also part of the model. The comparison with thermal pyrometer measurements shows that with respect to regions with high thermal load a qualitatively and quantitatively good agreement of the conjugate results and the measurements can be found. In particular, the region in the vicinity of the mid-span section is exposed to a higher thermal load, which requires further improvement of the cooling arrangement. Altogether the achieved results demonstrate that the conjugate calculation technique is applicable for reasonable prediction of three-dimensional thermal load of complex cooling configurations for blades.